Автоматические приборы, регуляторы и вычислительные системы: Справочное пособие - Кошарский Б. Д. Борис Давидович; Безновская Т. Х. Татьяна Хаскелевна; Бек В. А. Владимир Александрович; Горохова М. С. Маргарита Самойловна; Крастошевский З. М. Зуня Моисеевич (Ленинград, Машиностроение, 1976)
Авт. указ. на обороте тит. л.